2000
DOI: 10.1136/bjo.84.5.456
|View full text |Cite
|
Sign up to set email alerts
|

The Bristol shared care glaucoma study: outcome at follow up at 2 years

Abstract: Aim-To examine the outcome of care for patients with glaucoma followed up by the hospital eye service compared with those followed up by community optometrists. Methods-A randomised study with patients allocated to follow up by the hospital eye service or community optometrists was carried out in the former county of Avon in south west England. 403 patients with established or suspected primary open angle glaucoma attending Bristol Eye Hospital and meeting defined inclusion and exclusion criteria were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 10 publications
3
84
1
1
Order By: Relevance
“…10 In Bristol, specially trained and accredited glaucoma optometrists were shown to perform as well as the routine HES glaucoma review in the management of stable primary open-angle glaucoma and OHT, with no statistically significant difference in outcome. 11,12 However, the authors found that the optometrists were rather cautious in their approach, with a relatively high proportion of patients being referred back to the HES. 12 The authors concluded that glaucoma screening through community optometrists would not generate savings, and that shared care schemes were not more costeffective than HES care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 In Bristol, specially trained and accredited glaucoma optometrists were shown to perform as well as the routine HES glaucoma review in the management of stable primary open-angle glaucoma and OHT, with no statistically significant difference in outcome. 11,12 However, the authors found that the optometrists were rather cautious in their approach, with a relatively high proportion of patients being referred back to the HES. 12 The authors concluded that glaucoma screening through community optometrists would not generate savings, and that shared care schemes were not more costeffective than HES care.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 However, the authors found that the optometrists were rather cautious in their approach, with a relatively high proportion of patients being referred back to the HES. 12 The authors concluded that glaucoma screening through community optometrists would not generate savings, and that shared care schemes were not more costeffective than HES care. 12 This was in contrast with another report, which found that the accredited glaucoma optometrists reduced the number of glaucomasuspect referrals to the HES by 40%, and was able to save the NHS approximately d17 per patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In 2006, a national survey identified 66 secondary care-led glaucoma shared care schemes in operation in England, 36 of which employed optometrists in some capacity (14 in the community and 22 'in-house'). 14 To our knowledge, there have been two previous studies that have compared the management decisions made by optometrists working within the hospital glaucoma service with those of consultant ophthalmologists 4,11 and three involving specially trained community optometrists assessing new referrals, 8 diagnosed glaucoma/glaucoma suspect patients 9 , or a combination of both. 10 Although all of these optometrists had undergone additional training, as far as we are aware, none had completed the College of Optometrists Diploma in Glaucoma and the hospital-based optometrists were working alongside the consultant ophthalmologist who was responsible for the patients.…”
Section: Resultsmentioning
confidence: 99%
“…4,[9][10][11] It has been shown that specially trained community optometrists are able to make satisfactory decisions regarding the diagnosis and initiation of treatment for glaucoma 8 and can help to reduce the number of false positive referrals into the Hospital Eye Service (HES) by up to 53%. [5][6][7] However, there remains a large number of individuals considered to be at risk of developing glaucoma who are still being monitored within the HES and, once a diagnosis of glaucoma is confirmed, follow-up becomes lifelong.…”
Section: Resultsmentioning
confidence: 99%